Pengaruh Religiusitas, Pelayanan dan Transparansi Terhadap Minat Membayar Zakat Pada Baznas Asahan - siti masitoh (ITB AAS INDONESIA Surakarta, 2022)
The Asahan Regent hopes that with the zakat funds, zakat management should be better, professional and on target so that zakat institutions from the center to the regions gain public trust. He also urges the managers of zakat institutions to be able to collaborate with various related parties, including the government, organizations, community leaders, scholars and other parties so that any problems that occur can be given a solution. The type of research that will be conducted in this research is quantitative description. Religiosity has a significant and partial effect on interest. Service has a significant and partial effect on. Transparency has no significant and partial effect on interest.